Recombinant Antigen Targets for Serodiagnosis of African Swine Fever - Gallardo, Carmina; Reis, Ana L.; Kalema-Zikusoka, Gladys; Malta, Joana; Soler, Alejandro; Blanco, Esther; Parkhouse, R. M. E.; Leita, Alexandre (Clinical and Vaccine Immunology, 2009)
African swine fever (ASF) is an infectious and economically important disease of domestic pigs. There is no vaccine, and so reliable diagnosis is essential for control strategies. The performance of four recombinant ASF virus (ASFV) protein (pK205R, pB602L, p104R, and p54)-based enzyme-linked immunosorbent assays (ELISAs) was evaluated with European porcine field sera that had been established by Office International des Epizooties (OIE)-approved tests to be ASFV negative (n = 119) and ASFV positive (n = 80). The κ values showed that there was almost perfect agreement between the results of the “gold standard” test (immunoblotting) and the results obtained by the p54-specific ELISA (κ = 0.95; 95% confidence interval [CI], 0.90 to 0.99) and the pK205R-specific ELISA or the pB602L-specific ELISA (κ = 0.92; 95% CI, 0.86 to 0.97). For the pA104R-specific ELISA, there was substantial to almost perfect agreement (κ = 0.81; 95% CI, 0.72 to 0.89). Similar results were observed by the OIE-approved ELISA (κ = 0.89; 95% CI, 0.82 to 0.95). Importantly, antibodies against these proteins were detectable early after infection of domestic pigs. Preliminary testing of 9 positive and 17 negative serum samples from pigs from West Africa showed identical results by the recombinant protein-based ELISA and the OIE-approved tests. In contrast, there was a high degree of specificity but a surprisingly a low level of sensitivity with 7 positive and 342 negative serum samples from pigs from East Africa. With poorly preserved sera, only the p104R-specific ELISA showed a significant reduction in sensitivity compared to that of the OIE-approved ELISA. Finally, these recombinant proteins also detected antibodies in the sera of the majority of infected warthogs. Thus, recombinant ASFV proteins p54, pB602L, and pK205R provide sensitive and specific targets for the detection of antibodies in European and West African domestic pigs and warthogs.